A new Cyana Walker, 1854 from Vietnam (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel; Dubatolov, Vladimir V. (Zootaxa, 2017)
A new species of the genus Cyana Walker, 1854, C. aurantifascia Volynkin, Černý & Dubatolov, sp. nov. is described from Vietnam. The Cyana dohertyi and Cyana phaedra species-groups are established. The new species belongs to the C. dohertyi species-group. Diagnostic comparisons are made with species of similar habitus belonging to the same and to other species-group. Adults, male and female genitalia of the new and related species are illustrated.